KONSEP PSIKOLOGIS TENTANG TAHAP PERKEMBANGAN ANAK SEBAGAI LANDASAN PENDIDIKAN ISLAM - Salsabila , Ghina Fairuz; Tarwilah, Tarwilah; suraijiah, Suraijiah (Sasangga: Jurnal Pendidikan dan Pembelajaran, 2024)
This article discusses the concept of child development psychology as the basis of Islamic education. Child development psychology is a science that studies how children grow and develop physically, cognitively, linguistically, socially, and emotionally from conception to adulthood. A deep understanding of child development psychology is a very important foundation in Islamic education. So this study aims to explore the concept of child development psychology, analyze educational psychology in Islam, and collect data on child education from a psychological perspective. This study uses a qualitative method with a descriptive-analytical approach, and the theory used includes the concept of child development psychology as the basis of Islamic education. This study emphasizes the importance of an educator understanding child development psychology because it is the key to creating an optimal learning environment for each child. By applying the principles of developmental psychology, educators can help children grow into whole, intelligent, and well-characterized individuals. The results of the study show that the concept of child development psychology has a very important role in Islamic education. By understanding how children grow and develop, educators can create a conducive learning environment to help children achieve their best potential, both intellectually, socially, and spiritually.